Integrated curation and data mining for disease and phenotype models at the Rat Genome Database. (11th February 2019) - Wang, Shur-Jen; Laulederkind, Stanley J F; Zhao, Yiqing; Hayman, G Thomas; Smith, Jennifer R; Tutaj, Monika; Thota, Jyothi; Tutaj, Marek A; Hoffman, Matthew J; Bolton, Elizabeth R; De Pons, Jeffrey; Dwinell, Melinda R; et al.
Abstract: Rats have been used as research models in biomedical research for over 150 years. These disease models arise from naturally occurring mutations, selective breeding and, more recently, genome manipulation. Through the innovation of genome-editing technologies, genome-modified rats provide precision models of disease by disrupting or complementing targeted genes. To facilitate the use of these data produced from rat disease models, the Rat Genome Database (RGD) organizes rat strains and annotates these strains with disease and qualitative phenotype terms as well as quantitative phenotype measurements. From the curated quantitative data, the expected phenotype profile ranges were established through a meta-analysis pipeline using inbred rat strains in control conditions. The disease and qualitative phenotype annotations are propagated to their associated genes and alleles if applicable. Currently, RGD has curated nearly 1300 rat strains with disease/phenotype annotations and about 11% of them have known allele associations. All of the annotations (disease and phenotype) are integrated and displayed on the strain, gene and allele report pages. Finding disease and phenotype models at RGD can be done by searching for terms in the ontology browser, browsing the disease or phenotype ontology branches or entering keywords in the general search. Use cases are provided to show different targeted searches of rat strains at RGD.